Upaya Cegah Tangkal Perilaku Korupsi Melalui Psikoedukasi Berbasis Kearifan Lokal Tari Prajuritan - Yuwono, Emmanuel Satyo; Wibowo, Doddy Hendro (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2023)
Local culture can be a way to empower the character of honesty to prevent corrupt behavior. “Tari Prajuritan” is a dance art from Banyubiru Village, Semarang Regency which has a philosophical meaning of honesty. The purpose of this activity is to increase understanding and awareness to prevent corrupt behavior based on the values of the “Tari Prajuritan”. Participants in the activity were village officials, community leaders, religious leaders, and teachers. Activities carried out using psychoeducational methods, in the form of performances of the “Tari Prajuritan”, active lectures, and discussions. The implementation of psychoeducation is carried out by prioritizing togetherness and interactive discussions with participants. Participants were enthusiastic about participating in the activity until it was finished. The results of the activity evaluation show that similar activities can be carried out again by adding more participants, likely for students in schools so that the warrior dance culture can be more popularized and benefit more widely.